Clinical and functional outcome of metal backed versus all polyethylene post operated total knee replacement patients: a prospective study - Kriplani, Suresh; Patil, Tejas; Kulkarni, Milind; Kulkarni, G. S.; Kabra, Krishna; Parikh, Yash (International Journal of Research in Orthopaedics, 2020)
Background: Osteoarthritis (OA) is most common chronic degenerative disease in orthopaedic practice. The literature pertaining to comparison of the clinical outcome and functional outcome between the metal backed and all polyethylene prosthesis for the total knee replacement are scant. Methods: A prospective study was undertaken in a tertiary hospital April 2018 to June 2019. The final sample size was 32 cases (40 knees) of newly diagnosed of primary OA knee cases treated with cemented TKR with Metal backed prosthesis and 29 cases (40 knees) with all polyethylene prosthesis. The patients were followed up at 1st, 3rd and 6th post-operative months. Results: Knee clinical score pre-op was not statistically significant. But after 1 month, after 3 months after 6 months, knee clinical score was statistically significant. Knee functional score pre-op, after 1 month, after 3 months, after 6 months was not statistically significant. 87% patients of metal back total knee replacement and 85% of all poly total knee replacement had no pain or just mild pain. Conclusions: Total knee arthroplasty resulted in excellent relief of pain, range of motion, restoration of function, and low prevalence of complications and continues to function well during the follow-up period. Improvement in clinical score in MB group is correlated significantly than all polyethylene group. Knee society scoring system is an effective in evaluating clinical, functional outcomes.